The COVID-19-related challenges and coping strategies among international students: An integrative review - Almadadha, Lina; Golizadeh, Leila; Sheppard-Law, Suzanne (Journal of International Students, 2025)
This integrative review identifies COVID-19-related challenges among international university students and explores their coping strategies and university support. To the best of our knowledge, this integrative review is the first to address both the challenges encountered by international students during the pandemic comprehensively and their coping strategies. Using Whittemore and Knafl’s five-step integrative review method, a systematic search was conducted across six databases and Google Scholar in February 2025, yielding 26 relevant studies. Two main themes and six subthemes were identified. The first theme focuses on challenges, including financial, psychological, and online learning impacts, as well as discrimination. The second theme highlights coping strategies, encompassing self-developing coping strategies and university support. In conclusion, international students have encountered numerous challenges during the COVID-19 pandemic.